Metamorphoses of Hamiltonian systems with symmetries - Efstathiou Konstantinos (Berlin Springer-Verlag, 2005)
The book moves gradually from finding relative equilibria using symmetry, to the Hamiltonian Hopf bifurcation and its relation to monodromy and, finally, to generalizations of monodromy.
Keywords: Hamiltonian systems